Systemic exposure and urinary excretion of vanadium following perinatal subchronic exposure to vanadyl sulfate and sodium metavanadate via drinking water. (1st May 2022) - Waidyanatha, Suramya; Weber, Frank X.; Fallacara, Dawn M.; Harrington, James M.; Levine, Keith; Robinson, Veronica G.; Sparrow, Barney R.; Stout, Matthew D.; Fernando, Reshan; Hooth, Michelle J.; Xie, Guanhua; Roberts, Georgia K.
Abstract: Vanadium is a ubiquitous environmental contaminant although there are limited data to assess potential adverse human health impact following oral exposure. In support of studies investigating the subchronic toxicity of vanadyl sulfate (V 4+ ) and sodium metavanadate (V 5+ ) following perinatal exposure via drinking water in male and female rats, we have determined the internal exposure and urinary excretion of total vanadium at the end of study. Water consumption decreased with increasing exposure concentration following exposure to both compounds. Plasma and urine vanadium concentration normalized to total vanadium consumed per day increased with the exposure concentration of vanadyl sulfate and sodium metavanadate suggesting absorption increased as the exposure concentration increased. Additionally, females had higher concentrations than males (in plasma only for vanadyl sulfate exposure). Animals exposed to sodium metavanadate had up to 3-fold higher vanadium concentration in plasma and urine compared to vanadyl sulfate exposed animals, when normalized to total vanadium consumed per day, demonstrating differential absorption, distribution, metabolism, and excretion properties between V 5+ and V 4+ compounds. These data will aid in the interpretation of animal toxicity data of V 4+ and V 5+ compounds and determine the relevance of animal toxicity findings to human exposures. Highlights: Vanadium (V) is a ubiquitous environmental contaminant. Internal exposure was determined in rodents after oral exposure to V 4+ and V 5+ . Plasma and urine V levels increased more than proportional to V 4+ and V 5+ dose. Exposure to V 5+ caused up to 3-fold higher plasma and urine V levels than V 4+ . Data demonstrate differential ADME properties between V 5+ and V 4+ compounds.